Functional-pagmatic characteristics of the mediatext - Butova A. V. (Education and Pedagogy, 2020)
a special direction in linguistics – media linguistics – deals with the analysis of media texts. The purpose of this article is to consider the functional and pragmatic characteristics of media texts. Particular attention is paid to the tasks and functions that the media text performs in the mass media discourse. The types of media texts and their linguistic and stylistic features are considered.
Keywords: масс-медиальный дискурс; медиатекст; медиалингвистика; функции медиатекста; типы медиатекстов; media linguistics; mass media discourse; media text; functions of media text; types of media texts